Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisis DI RSUD Dr. Soehadi Prijonegoro Sragen - Ika Hayun Al Aziz; Sudiro Sudiro (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Family Support, Level Of Anxiety, Chronic Renal Failure, And Hemodialysis. Chronic kidney disease is a threat for human because the prevalency increase every years. Patient of chronic kidney disease with teraphy hemodialysis can cause psychological pressure pasca hemodialysis. One example of psychological pressure is anxiety. For decrease anxiety of patient with terapy hemodialysis need family support. Objectives To identity the relationship among family support with level of anxiety chronic renal failure of patients with therapy hemodialisis in Dr.Soehadi Prijonegoro Hospital. Methods Design of the research used descriptive analytic with cross sectional approach. The sampling method is total sampling. Instrument that used for measure level anxiety and family support is a questionnaire. Analysis for data used Kendall Tau. Ressearch result The majority of family support level is good with amount 38 (70,4%). The majority of level anxiety is not anxiety with amount 38 (70,4%).The result of kendall tau is α : 0,000, τ : 0,865.Conclusion There is relationship between family support with level of anxiety chronic renal failure of patients with therapy hemodialysis.